Peran Organisasi IPNU-IPPNU Ranting Bluri dalam Membentuk Karakter Religius Remaja melalui Jami’yah Khitobah dan Jami’yah Tahlil Keliling - Nuri Dwi Aprilia Safitri; Ahamd Maujuhan Syah; Ainur Rofiq (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
Religious character is something that someone should have, especially for teenagers. One of the important parts of religious character for a teenager is carrying out religious deeds in everyday life. As is the case with the IPNU-IPPNU Ranting Bluri organization which is a religious-based organization, wherein the organization activities are carried out as a means as well as a forum for developing religious character for teenagers in the form of Jam'iyah Khitobah and Jam'iyah Tahlil Keliling activities which are carried out regularly every week. The formulation of the problem in this study, namely (1) the implementation of activities that can shape the religious character of adolescents (2) the factors that influence the formation of the religious character of adolescents in the IPNU-IPPNU Organization of the Bluri Branch through jam'iyah khitobah and jam'iyah tahlil in Bluri Village Solokuro Lamongan. This research uses a design with a qualitative approach and the type of research is a case study. The subjects in this study were active members of IPNU-IPPNU with a total of 4 people using a purposive sampling technique which aims to see how the process of carrying out activities that can shape religious character and what are the factors that influence the process of forming religious character in the IPNU-IPPNU Ranting Bluri Organization. . The instruments used in this research are interviews and observations that have been determined with a purposive sampling technique. Wetness checking of the data used is to increase persistence and triangulation. The results of this study are: 1) The process of forming adolescent religious characters in the jam'iyah khitobah activities are sholawatan, reading manaqib, learning speeches with Islamic themes. At jam'iyah tahlil around the activities are tahlilan, completing the Qur'an, praying in congregation, dhibaan, and giving alms. 2) internal factors and external factors.